Hypocholesterolemia in cats: a multicenter retrospective study of 106 cats. Issue 8 (August 2020) - Bowman, Claudia; Viall, Austin; Rudinsky, Adam; Gilor, Chen; Palerme, Jean-Sébastien
Objectives: The aim of this study was to describe the clinicopathologic findings and associated diseases found in a population of hypocholesterolemic cats referred to two tertiary care facilities. Methods: An electronic medical record search was performed at two veterinary university referral centers to identify cats with serum cholesterol values below the reference interval between January 2004 and 2016. Clinicopathologic data were reviewed for each case and cats were classified into specific disease categories based on clinical diagnosis. Median cholesterol values were compared between disease categories, as well as between survivors and non-survivors. Results: In total, 106 hypocholesterolemic cats were included. The median age of the cats was 6 years (range 0.24–18 years). The most common disease categories were gastrointestinal (25.9%), hepatobiliary (19.8%), hematologic (14.8%) and urogenital (14.8%). Though median serum cholesterol values did not differ significantly between survivors and non-survivors, cats with concurrent hypoalbuminemia were at higher risk (odds ratio 15.6, 95% confidence interval 5.2–46.6; P <0.0001) of not surviving to discharge than cats with normal serum albumin concentrations. Conclusions and relevance: Taken together, our data suggest that while the degree of hypocholesterolemia did not appear to influence survival rates, the concurrent presence of hypocholesterolemia and hypoalbuminemia was associated with a worse prognosis.